PENGEMBANGAN APLIKASI OPERASIONAL RESTORAN DENGAN FRAMEWORK SCRUM (STUDI KASUS: RESTORAN PT.XYZ) - Ngurah Suryantara, I Gusti; Michael, Michael; Andry, Johanes Fernandes; Ginting, Jusia Amanda (Infotech: Journal of Technology Information, 2023)
In software development, it is necessary to plan carefully, so that the software developed is in accordance with user needs. Software development without good planning will result in a patchwork of software development. To avoid the patchwork of software development, a software development framework is required. The research "Developing Restaurant Operational Applications With Scrum Framework (Case Study: PT.XYZ Restaurant)" aims to develop restaurant operational software at PT. XYZ. The software development framework used in software development uses the Scrum framework. The Scrum framework is a variant of the Agile framework. Agile has a dynamic way of working (iterative and incremental). The Scrum framework has a product backlog, then the product backlog is divided into several sprints. One sprint will be run in one iteration, so that each end of a product sprint that meets the definition of “Done” must be achieved. The use of the Scrum framework emphasizes communication and collaboration between various stakeholders. The result of this research is a software that helps restaurant operations at PT. XYZ starting from master files, transactions files, to reports files. By using the Scrum framework in application development, the application development life cycle is created. Software development can be done by implementing an enterprise architecture that already belongs to a company. Data architecture, application architecture, and technology architecture as the basis for application development in the enterprise